A new species of Ozoroa (Anacardiaceae: Anacardioideae) from Maputaland, South Africa - Boon, Richard G.c.; van Wyk, Abraham E. (Phytotaxa, 2025)
Ozoroa bhangazica, a clonal, fire-adapted geoxylic suffrutex, is formally described as a new species with a highly restricted distribution in the Maputaland Centre of Endemism in KwaZulu-Natal Province, South Africa. It is confined to Maputaland Wooded Grassland on Quaternary coastal sands, a vegetation type notable for its rich diversity of geoxylic suffrutices. The two known populations are included in the iSimangaliso Wetland Park, a World Heritage Site. In southern Africa, Ozoroa species are divided into two groups based on leaf and pollen characters; O. bhangazica belongs to Group A and is unique among KwaZulu-Natal species for its geoxylic growth form. The genus shows significant infraspecific vegetative variation, with O. bhangazica displaying distinct variation in leaf size and shape between new shoots after fire and regrowth that has persisted through one or more fire-free seasons. Morphologically, the new species resembles O. barbertonensis, another geoxylic suffrutex, which is a geographically isolated serpentine endemic confined to the Barberton Centre of Endemism about 250 km from where O. bhangazica occurs. Both share the characteristic of linear to narrowly oblong leaves following fire. However, O. bhangazica can be distinguished by its longer, broader leaves, which are mostly glabrous on the upper surface with flat (non-revolute) margins, a longer petiole, and larger mature drupes. A provisional conservation status of Near Threatened (NT) is recommended under IUCN Red List criteria.